Comparison of methods to evaluate implant-abutment interface - Karina Oliveira de Faria; Clébio Domingues da Silveira Júnior; João Paulo da Silva Neto; Maria da Glória Chiarello de Mattos; Marlete Ribeiro da Silva; Flávio Domingues das Neves (Universidade Estadual de Campinas, 2015)
Aim: To compare two main methods of two-dimensional measurement of fit at the implant prosthodontic interface, testing the hypothesis that optical microscopy (OM) can reliably and efficiently scanning electronic microscopy (SEM). Methods: Four frameworks with four titanium abutments joined with titanium bars were used. The implant-abutment interfaces were examined by three different methods, forming 3 groups: analysis by OM (40x), and analysis by SEM at 300x and 500x. Readings were taken at the mesial and distal proximal surfaces on the horizontal and vertical axes of each implant (n=32). One-way ANOVA with a significance level of 5% was used for statistical analysis. Results: Neither the horizontal fit nor vertical fit values of the 3 groups presented statistically significant differences (p=0.410 and p=0.543). Conclusions: OM was found to be an accurate two-dimensional method for abutment-framework or implant-abutment interface measurements, with lower costs than SEM. SEM micrographs at 500x presented technical difficulties for the readings that might produce different results.